Forestry Research - Tewari, D. N. (Indian Forester, 1991)
The forestry research in India has by now a history of more than a century. Outstanding work has been done in tbe past. However current knowledge and pattern of research will not result sufficiently accurate predictions of the consequences of potentially harmful influences on forest-management practices that lack a sound basis in biological knowledge. The deficiency will reduce our ability to maintain or enhance forest productivity, recretion, and conservation as well as our ability to ameliorate or adapt to changes in the global environment. To help overcome this unfortunate deficiency in knowledge, a new research paradigm will need to be adopted-an environmental paradigm. This will require forestry research to increase the breadth of research areas covered and the depth to which they are investigated. Formation of Indian Council of Forestry Research and Eduucatlon (ICFRE) and Integration of forestry research, education and extension with increased funding will bring golden and green era in Indian Forestry.